Double potential step chronoamperometry at a microband electrode: Theory and experiment - Barnes, E; Xiong, L; Ward, K; Compton, R (2013)
Numerical simulation is used to characterise double potential step chronoamperometry at a microband electrode for a simple redox process A + e- goes to B, under conditions of full support such that diffusion is the only active form of mass transport. The method is shown to be highly sensitive for the measurement of the diffusion coefficient of both A and B, and is applied to the one electron reduction of decamethylferrocene (DMFc), DMFc - e- goes to DMFc+, in the room temperature ionic liquid 1-propyl-3-methylimidazolium bistrifluoromethylsulfonylimide. Theory and experiment are seen to be in excellent agreement and the following values of the diffusion coefficients were measured at 298 K: D_(DMFc) = 2.50 x 10^(-7) cm^(2) s^(-1) and D_(DMFc+) = 9.50 x 10^(-8) cm^(2) s^(-1).